A Salivary Calcium Binding Protein in Patients with Oral Squamous Cell Carcinoma in Relation to Smoking - Edan, Wisam H; El-Samarrai, Sulafa K (Journal of Baghdad College of Dentistry, 2016)
Background: The present study aimed to assess the distribution, prevalence, severity of malocclusion in Baghdad governorate in relation to gender and residencyMaterials and Methods: A multi-stage stratified sampling technique was used in this investigation to make the sample a representative of target population. The sample consisted of 2700 (1349 males and 1351 females) intermediate school students aged 13 years representing 3% of the total target population. A questionnaire was used to determine the perception of occlusion and orthodontic treatment demand of the students and the assessment procedures for occlusal features by direct intraoral measurement using veriner and an instrument to measure the rotated and displaced teeth.Results and conclusions: The presence of malaligned teeth was reported by 39% of the sample. The most prevalent reported types of malaligned teeth were spaced teeth (26.6%); Of the students who stated that they have malaligned teeth, 70.3% thought that it affected their appearance, 17.8% affected chewing, and 7.8% affected speech; The most common reasons for not seeking orthodontic treatment were the thought that treatment is not important or not possible (25.8%) and fear of pain (48.8%).One or more missing teeth due to extraction or trauma were found in 4.9% of the sample,the most common extracted tooth was the mandibular first molar. Crowding was more concentrated in the lower anterior segment while the spacing cases were higher and more concentrated in the upper anterior segment. A maxillary central diastema was found in 18.1 % of the sample with a mean of 0.306 mm. Anterior irregularities were found in (18.36 %maxillary and 26.84% mandibular),mean overjet 3.310 mm, mean overbite was 2.99 mm, Class I Angle class was found in 78.29%, class II in 19.5% and class III in 2.3%. Posterior crossbite found in 5.6%, anterior openbite (1.7%) and midline shift (54.34 %).Normal lip form was found in 86.6%, soft tissue impingement in 3.3%.The treatment need according to DAI show that 72.3% of the sample were found to have no or slight treatment need, 15.9% with treatment elective, 7.3% with treatment highly desirable, and 4.5% with treatment mandatory.Also increase the need and decrease demand for orthodontic treatment among adolescents in the Baghdad commune. This data will be useful for public oral health service and emphasize the need for orthodontic treatment among Baghdadi adolescents.